STUDIES ON A NOVEL RECOMBINANT LIPASE A FROM BACILLUS SUBTILIS FS2 - Phung Thu Nguyet; Nguyen Hong Thanh; Truong Nam Hai; Jan-Christer Janson (Universitas Gadjah Mada, 2008)
A strain of Bacillus subtilis FS2 isolated from a traditional fish source in Vietnam has been shown to produce an enzyme possessing both a gelatinase and a lipase A (LipA) activity when tested on agar plates containing 0.1% tributyrin and 0.3% gelatine. A gene encoding LipA was isolated and expressed in E. coli BL21 (DE3). The enzyme has got an apparent Mr of 24 kDa, a pI of 9.2 and was purified to electrophoretical homogeneity by affinity chromatography. Both the lipase and the gelatinase showed optimum activity at pH 10 and at 30 0 C, with highest activity in the range 25-37°C. The metal ions Fe++, Co++, and Mn++ at 10 mM had strong inhibitory effect on both activities whereas Ca++ had no effect and Zn++ had a slight enhancing effect. The specific enzymatic activities obtained were 19814 U/mg for the lipase and 1245 U/mg for the gelatinase.